Sundanese Local Wisdom In The Activities of Rebo Nyunda and its Potential For Education Tourism Purposes - Kurniawaty, Imas; Dahliyana, Asep; Faiz, Aiman (Universitas Pendidikan Indonesia, 2021)
Local wisdom is a good relationship between humans, nature, and the environment in an area influenced by culture. In the context of developments to maintain the local culture, one can be done with a tourism approach. The policy of Bandung Masagi with Rebo Nyunda program implemented in the world of bureaucracy and schools can be developed into a new tour to introduce Sundanese culture. The approach used to acquire data is qualitative with case study methods. The results illustrate that the Rebo Nyunda program implemented in schools can be used as a cultural tour by complementing the shortage of programs that tend to be formal and rigid. It is important to increase the appeal for the outside community in getting to know the local wisdom of Sundanese through educational institutions with more introducing symbols, languages, behavioral ordinances, and games of Sundanese children